OS 22-08 Prevalence of primary aldosteronism and its cardio-metabolic factors Chinese hypertensive patients in Xinjiang of China. (September 2016) - Li, Nanfang; Yao, Xiaoguang; Zhou, Ling; Abulikem, Suofeiya; Zhang, Delian; Chang, Guijuan; Zhou, Keming
Abstract : Objective: To investigated the prevalence of primary aldosteronism (PA) and compare the pattern of PA patients with essential hypertension regarding clinical data in general hypertensive patients in Xinjiang of China. Design and Method: Consecutive hypertensive patients referred to Hypertension Center of Xinjiang from 2009 to 2011 underwent a diagnostic protocol composed of measurement of Na + and K + in serum and 24-h urine, sitting plasma renin activity, and aldosterone at baseline and after saline loading test. The patients with an aldosterone/renin ratio >20 at baseline, and/or >5 after saline loading test, and adrenal vein sampling (AVS). Patients were evaluated for glucose, lipid profile, smoking and alcoholism and the clinical profiles were compared between PA and HBP group. Results: (1) 474 (28.03%) out of 1677 hypertensive patients were diagnosed PA.(2) 25.4% females with hypertension were identified PA, the detection rate of PA was around 30% in OSAS, obese, age<45 yr and hyperglycemia population, respectively.(3) The patients of PA showed worse blood control, lower serum K + (3.72 ± 0.38mmol/L), higher urine K + excretion (42.68 ± 16.62 mmol/L) compared to HBP. 197 (43.2%) were obese in PA patients with a mean BMI of 27.43 ± 3.67 kg/m 2 and 416 (35.6%) were obese with a mean BMI of 26.87 ± 3.77 kg/m 2 in HBP group, but the fasting glucose, TC and LDL-C showed higher levels in patients with HBP. 43.2% PA patients and 35.6% HBP patients were diagnosed of OSAS (AHI > 5).(4) Multivariate logistic regression analysis showed that abnormal presence of adrenal CT, hypokalemia history, family history of hypertension and severity of OSAS would increase the risk of PA. Conclusions: A markedly prevalence of PA (28.03%) was detected in Chinese general hypertensive population, the greater detection rate of PA in males and patients with severe OSAS leading to a concept that PA identification should extend to such individuals.